Islam dan Revolusi Digital: Studi Analisis terhadap Fenomena Artificial Intelligence dalam Perspektif Pendidikan Islam - Shaieba, Halya Quzwainie; Al-Ahqaf, Muhammad Infithar (Proceeding of International Conference on Islamic Education (ICIED); Vol 10 No 1 (2025): Proceeding of International Conference on Islamic Education (ICIED), 2025)
The development of Artificial Intelligence (AI) has brought significant transformations in various sectors of life, including Islamic education. This study aims to analyze the phenomenon of AI in the perspective of Islamic education, examining the technical, pedagogical, philosophical, ethical, and spiritual aspects that are central to Islamic education. The method used is a literature study with a qualitative approach. Data were collected through literature searches on the academic databases Google Scholar, SCOPUS, ELSEVIER, and Connected Papers with a publication range of 2020-2025. From the initial 40 articles, a systematic selection was made following the PRISMA guidelines, resulting in 20 articles to be analyzed using thematic analysis methods. The results of the study show that AI has significant potential to improve learning access, efficiency, and personalization in Islamic education through applications such as digital interpretation and interactive e-learning platforms. However, serious challenges were also found in the form of the risk of technological dependence, which can weaken critical thinking skills, reduce teacher-student interaction, and erode the values of tarbiyah, ta'lim, and ta'dib, which are the essence of Islamic education. This study concludes that the integration of AI in Islamic education must be carried out in a balanced manner by positioning AI as a means (wasilah) rather than an end (ghayah), accompanied by clear institutional policies, the development of digital ethics awareness, and a curriculum that integrates technology with Islamic values to ensure that AI strengthens, rather than replaces, the essence of Islamic education, which balances knowledge, faith, and righteous deeds.